Essays on Indo-Aryan Mythology - Aiyangar, Narayan, (Brill | Manohar Publishers & Distributors, 2024)
Essays on Indo-Aryan Mythology explores various aspects of Indo-Aryan mythology prevalent during the ancient times. The first part focuses on the Vedic gods and goddesses. The essays in this book contains the description of Vishnu's incarnations. These essays delve into their stories, their symbolism, and the rituals associated with their worship. Throughout the book, a wide range of sources, particularly Vedic and Puranic texts, as well as archaeological and anthropological evidence are used to narrate the stories of Indian gods and goddesses. The book also provides detailed descriptions of the Sanskrit terminologies that are central to Indo-Aryan mythology, making the book accessible to both scholars and general readers.